Analysis of the Role of MI Teachers in Developing Students' Social-Emotional Character in the Digital Age: A Literature Review - Fatimah Aristiati (ALSYS, 2025)
The digital era has introduced new challenges for education, particularly in shaping the social-emotional character of Madrasah Ibtidaiyah (MI) students. Amid the rapid development of information technology, MI teachers are expected to serve not only as learning facilitators but also as counselors capable of integrating social and emotional values into the educational process. This study aims to comprehensively analyze the role of MI teachers in developing students’ social-emotional character in the digital age, with a focus on strategies, approaches, and challenges encountered. A Systematic Literature Review (SLR) method was employed, analyzing a range of scholarly journals, articles, and relevant references published between 2019 and 2025. The findings indicate that teachers play a vital role in instilling character values through active learning strategies, project-based learning, the mindful use of digital media, and collaboration with parents and the community. Digitally literate teachers who model ethical behavior in the digital space are shown to be more effective in fostering empathy, responsibility, and social skills among students. The study concludes that strengthening the social-emotional character of MI students in the digital era requires a synergy of relevant pedagogical approaches, purposeful integration of technology, and support from a positive, collaborative learning environment. These findings offer both practical and theoretical contributions for teachers, educational institutions, and policymakers in designing adaptive character education strategies that address contemporary challenges.